Answer:
a = Not a solution
b = Solution
c = Solution
d = Not a solution
Explanation:
Here we are given with two equations so lets call them equation 1 and 2
3x_1 + 8x_2 - 14x_3=9-------(1)
x_1 + 3x_2 - 4x_3 = 1--------(2)
Part (a)
For values: (6-2s_1, 5+3s_1 , s_1)
Putting the values in Equation (2) for convenience however it can also be solved by substituting in Equation (1).
6-2s_1 + 3(5+3s_1) - 4s_1 = 1
6-2s_1 + 15 + 9s_1 - 4s_1 = 1
21+3s_1 = 1
L.H.S ≠ R.H.S
Hence not a solution
Part (b)
For values: (-11-5s_(1,) s_1,(-(6+s_1 ))/2)
11-5s_1 + 3s_1 - 4(-(6+s_1)/2) = 1
-11-5s_1 + 3s_1 + 12+2s_1 = 1
1 = 1
L.H.S = R.H.S
Hence it has a solution
Part (c)
For values:(19+10s_1,-6-2s_1,s_1)
19 + 10s_1 + 3(-6-2s_1) - 4s_1 = 1
19 + 10s_1 - 18 - 6s_1 - 4s_1 = 1
1 = 1
L.H.S = R.H.S
Hence it has a solution
Part (d)
For values: ((5-(4s_1)/3 , s_1, -(7-s_1)/4)
((5-4s_1)/3) + 3s_1 - 4(-(7-s_1)/4)) = 1
5/3 - 4/3s_1 + 3s_1 + 7-s_1 = 1
5/3 + 7- (4/3s_1) + 2s_1 = 1
L.H.S ≠ R.H.S
There is no need to simplify this any further as it can be seen it has no solution.